Silicon Increases Leaf Chlorophyll Content and Iron Nutritional Efficiency and Reduces Iron Deficiency in Sorghum Plants - Teixeira, Gelza Carliane Marques [UNESP]; de Mello Prado, Renato [UNESP]; Oliveira, Kamilla Silva [UNESP]; D’Amico-Damião, Victor [UNESP]; da Silveira Sousa Junior, Gilmar [UNESP] (Springer Nature, 2020)
The objective of this study was to evaluate the effect of silicon (Si) on iron (Fe) deficiency in sorghum plants grown in a nutrient solution, seeing that sorghum crops are sensitive to iron deficiency and Si may alleviate this deficiency. Nonetheless, the nutritional mechanisms underlying this process have not been fully elucidated in this plant species. Treatments were arranged in a 2 × 2 factorial scheme and completely randomized block design, in the absence or presence of Si (2 mmol L−1) and under Fe deficiency or sufficiency, with five repetitions. The sources of Si and Fe were stabilized sorbitol sodium and potassium silicate (Si = 113.4 g L−1) and Fe-EDDHA chelate (Fe = 6%), respectively. The plants were cultured in pots filled with washed sand, and Si was supplied via nutrient solution at a concentration of 2 mmol L−1. The concentrations of Fe used in this study were 368 μmol L−1 for sufficiency conditions and 55.2 μmol L−1 for deficiency conditions. Our results showed that Si has a beneficial effect on sorghum plants under Fe deficiency by increasing the chlorophyll content and decreasing concentration of malondialdehyde (MDA). In addition, the application of Si increased the efficiency of translocation and utilization of Fe in plants under this micronutrient deficiency. In conclusion, Si reduced Fe deficiency in sorghum plants by increasing the concentration of photosynthetic pigments, reducing lipid peroxidation, improving the efficiency of Fe translocation and utilization, and resulting in a greater dry weight accumulation.
Keywords: Abiotic stress; Beneficial element; Ferric chlorosis; Plant nutrition; Sorghum bicolor L